Examining the global status of West Nile Virus with focus on current challenges in disease prevention in humans and animals - Zook, Stacey (Kansas State University, 2019)
West Nile virus (WNV) continues to be a worldwide threat to the health of humans and animals. The virus has been known to cause disease in humans since 1937, and its range continues to expand. While infection is typically asymptomatic, this virus can cause serious illness and death in the host. There are also significant expenditures of resources to control and prevent its morbidity in humans, domestic animals, and wildlife. It is a mosquito-borne disease with many challenges for surveillance and control that include some underlying issues with climate change. Currently, there are no licensed vaccines for humans or treatments for infection beyond supportive care, but there are several licensed vaccines for use in animals. The purpose of this report is to examine the global status of WNV and the current challenges of controlling this disease threat in humans and animals. This report will also review new strategies in vaccine development and other preventative measures.
Keywords: West Nile virus; Neuroinvasive disease; One health; Vaccine; Arbovirus; Culex